History of Costa Rica-Peru Diplomatic Relations during the National Campaign against the Filibusters (1856-1857): The Peruvian loan’s case - Mora-Ugalde, Sara (2021)
This article aims to study the diplomatic history between Costa Rica and Peru during the campaign against the filibusters, particularlythe Peruvian loan case. This study included diplomatic correspondence and some works of Costa Rican and Peruvian authors in which this subject was analyzed. By using discourse analysis, categories were established to identify the main reasons why this South American country conceded a loan to Costa Rica. These reasons were expressed mainly by the Peruvian Minister Pedro Gálvez, showing an evolvement in the justifications for the loan, starting with the characterization of Costa Rica, continuing with issues about the armed conflict at that time, to finally expose qualities attributed to Peru that reinforced the convenience of securing help to the Central American country.